A numerical investigation of elastoplastic deformation of cracks in tubular specimens subjected to combined torsional and axial loading. (October 2016) - Floros, Dimosthenis; Ekberg, Anders; Runesson, Kenneth
Highlights: Plastic crack face deformation in multiaxial loading numerically assessed. Evolution of crack face displacements established. Trends in experimental crack growth studies linked to simulation results. Shakedown/ratcheting in accumulated crack face displacements found. Predicted crack deflection linked to fractographic findings in literature. Abstract: Numerical simulations to investigate crack deformation in a pre-cracked cylindrical specimen subjected to mixed mode axial/torsional loading are carried out. Results are quantified in terms of crack face displacements and contrasted to experimental trends in the literature. The results aid in the understanding and interpretation of experimental results, in design of future experiments and in the development of models to predict mixed mode crack propagation. The analyses identify elastoplastic phenomena as major mechanisms to explain experimental results of mixed mode crack growth. These phenomena are interlinked in the general case, which significantly complicates the development of a general engineering model.